Antimicrobial photodynamic therapy and deproteinization in teeth with molar incisor hypomineralization: a case series - Mandetta, Amanda Rafaelly Honório; Bortoletto, Carolina Carvalho; Sobral, Ana Paula Taboada; Gimenez, Thais; Ribeiro, Caroline Diniz Pagani Vieira; Motta, Lara Jansiski; Horliana, Anna Carolina Ratto Tempestini; Mesquita-Ferrari, Raquel Agnelli; Prates, Renato Araujo; Deana, Alessandro Melo; Duran, Cinthya Cosme Gutierrez; Cordeiro, Rita de Cássia Loiola [UNESP]; et al. (AME Publishing Company, 2025)
Background: Molar incisor hypomineralization (MIH) is a complex developmental enamel defect influenced by various factors, including genetic predisposition. This condition primarily affects the first permanent molars and, in some instances, the permanent incisors. In this case series, we examined the clinical effects of antimicrobial photodynamic therapy (aPDT) and deproteinization with Papacárie on teeth with MIH and carious lesions, focusing on decontamination, hypersensitivity control, and restoration longevity with the use of minimally invasive techniques. Case Description: Seven permanent first molars from children aged 7 to 10 years, with carious dentin lesions and post-eruptive fractures, which required restorative clinical treatment, were selected. Selective chemical-mechanical removal of carious tissue and deproteinization were performed using PapacárieTM, followed by aPDT. A laser device was used, which emitted red light (wavelength: 660 nm, 100 mW, 6 J per spot, 3,571 mW/cm2, 214 J/cm2, 60 seconds). The teeth were then restored with a combined method involving resin-modified glass ionomer cement and bulk-fill composite resin. Microbiological analysis was conducted, along with the assessment of hypersensitivity using the Visual Analog Scale (VAS) and Schiff Cold Air Sensitivity Scale (SCASS) scales, and the evaluation of the longevity of restorations according to the criteria of the United States Public Health Service (USPHS). Clinical evaluations were performed after 48 hours, 3 months, and 6 months. Conclusions: aPDT proved to be promising treatment for decontamination and hypersensitivity control in molars with hypomineralization and dentinal caries. Moreover, deproteinization with Papacárie offers a promising, minimally invasive approach for enhancing restoration longevity.
Keywords: case series; dental atraumatic restorative treatment; hypersensitivity; Molar incisor hypomineralization (MIH); photochemotherapy